2012
DOI: 10.1007/s10585-012-9506-0
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole prevents triple-negative breast-cancer progression

Abstract: Dipyridamole is a widely prescribed drug in ischemic disorders, and it is here investigated for potential clinical use as a new treatment for breast cancer. Xenograft mice bearing triple-negative breast cancer 4T1-Luc or MDA-MB-231T cells were generated. In these in vivo models, dipyridamole effects were investigated for primary tumor growth, metastasis formation, cell cycle, apoptosis, signaling pathways, immune cell infiltration, and serum inflammatory cytokines levels. Dipyridamole significantly reduced pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 49 publications
2
42
1
Order By: Relevance
“…Dipyridamole been shown to potentiate classical chemotherapeutic drugs mainly through P-gp modulation and by blocking nucleoside transport (47). Recently, it was shown that dipyridamole alone delays tumor growth in breast cancer xenografts (48), but in our hands, using low micromolar concentrations, dipyridamole did not have appreciable anticancer activity as a single agent. This is in line with the observation that dipyridamole's antiproliferative effects were only observed when tumor cells were simultaneously challenged with statin, thereby triggering the feedback loop that was suppressed by the addition of dipyridamole.…”
Section: Discussionmentioning
confidence: 55%
“…Dipyridamole been shown to potentiate classical chemotherapeutic drugs mainly through P-gp modulation and by blocking nucleoside transport (47). Recently, it was shown that dipyridamole alone delays tumor growth in breast cancer xenografts (48), but in our hands, using low micromolar concentrations, dipyridamole did not have appreciable anticancer activity as a single agent. This is in line with the observation that dipyridamole's antiproliferative effects were only observed when tumor cells were simultaneously challenged with statin, thereby triggering the feedback loop that was suppressed by the addition of dipyridamole.…”
Section: Discussionmentioning
confidence: 55%
“…dipyridamole and bindarit), or at interfering with their immunosuppressive functions (celocoxib), or killing MDSCs (5 fluorouracil-or 5FU). Interestingly, dipyridamole [118] and bindarit [119] decrease the infiltration not only of MDSCs but also of TAMs in breast and prostate cancer proof of concept animal model studies.…”
Section: Molecular Network In the Tumor Microenvironmentmentioning
confidence: 94%
“…The anticancer effects of aspirin may be related to anti-platelet effects via irreversible inhibition of COX-1 [172173], and there is also some evidence that other anti-platelet agents, such as low molecular weight heparins and dipyridamole may also have anti-cancer or anti-metastatic activity [174176]. Beta-adrenergic receptor antagonists are also known to have effects on platelet aggregation and a meta-analysis published in 2014 showed that they decreased platelet aggregation by 13% (95% CI = 8 - 17%, standardised mean difference=-0.54, 95% CI = -0.85 – -0.24, P < 0.0001) [177].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%